Biotechnology changing life through science - Lerner, K. Lee.; Lerner, Brenda Wilmoth (Detroit : Thomson Gale, 2007)
Covers biotechnological applications ranging across medicine, agriculture, and industry. Devoted to helping younger students and general readers understand the fast-developing science and issues related to: advances in biotechnology, the science of molecular biology and genetics.
Ηλεκτρονικό βιβλίο
Keywords: Biotechnology -- Juvenile literature; Electronic books